Perceived neighbourhood food access is associated with consumption of animal-flesh food, fruits and vegetables among mothers and young children in peri-urban Cambodia. Issue 3 (1st March 2022) - Duong, Minh-Cam; Nguyen-Viet, Hung; Grace, Delia; Ty, Chhay; Sokchea, Huy; Sina, Vor; Young, Melissa F
Abstract: Objective: To examine whether mothers' perceived neighbourhood food access is associated with their own and their young children's consumption of animal-flesh food, fruits and vegetables in peri-urban areas of Cambodia. Design: A cross-sectional survey measured food consumption frequency and perceived neighbourhood food access, the latter including six dimensions of food availability, affordability, convenience, quality, safety and desirability. Multivariate logistic regression was used to assess the association between perceived food access and food consumption. Setting: Peri-urban districts of Phnom Penh and Siem Reap, Cambodia Participants: 198 mothers of children between 6 and 24 months old. Results: Over 25 % of the mothers and 40 % of the children had low consumption (< once a day) of either animal-flesh food or fruits and vegetables. Compared with perceived high food access, perceived low food access was associated with an adjusted 5·6-fold and 4·3-fold greater odds of low animal-flesh food consumption among mothers (95 % CI 2·54, 12·46) and children (95 % CI 2·20, 8·60), respectively. Similarly, relative to perceived high food access, perceived low food access was associated with 7·6-times and 5·1-times higher adjusted odds of low fruits and vegetables consumption among mothers (95 % CI 3·22, 18·02) and children (95 % CI 2·69, 9·83), respectively. Conclusions: Mothers' perceived neighbourhood food access was an important predictor of their own and their young children's nutrient-rich food consumption in peri-urban Cambodia. Future work is needed to confirm our findings in other urban settings and examine the role of neighbourhood food environment in the consumption of both nutrient-rich and nutrient-poor food.